Synthesis of metal-organic frameworks by continuous flow - Bayliss, Peter A.; Ibarra, I.A.; Perez, E.; Yang, S.; Tang, Chiu C.; Poliakoff, Martyn; Schröder, Martin (Royal Society of Chemistry, 2014)
A continuous flow process for the synthesis of a metal-organic framework using only water as the reaction medium and requiring only short residence times is described. This affords a new route to scale-up of materials incorporating many of the principles of green chemistry. The process is demonstrated by the synthesis MIL-53(Al) via continuous flow reaction requiring only 5-6 minutes with a space time yield of 1300 kg m-3 d-1. We have demonstrated the synthesis of 500 g of MIL-53(Al) using this process, which can be scaled-up further by simply feeding further solutions of metal salt and ligand through the reactor. The product has a higher surface area and a better colour than a commercially produced sample of this MOF. In addition, a new and effective method for the extraction of terephthalic acid from within the pores of MIL-53(Al) using supercritical ethanol has been developed, representing a new methodology for activation and removal of substrates from porous hosts.